Burden of Human Papillomavirus (HPV)-Related Cancers Attributable to HPVs 6/11/16/18/31/33/45/52 and 58. Issue 4 (7th January 2019) - de Sanjosé, Silvia; Serrano, Beatriz; Tous, Sara; Alejo, Maria; Lloveras, Belén; Quirós, Beatriz; Clavero, Omar; Vidal, August; Ferrándiz-Pulido, Carla; Pavón, Miquel Ángel; Holzinger, Dana; Halec, Gordana; et al.
Abstract: Background: Many countries, mainly high- and upper-middle income, have implemented human papillomavirus (HPV) vaccination programs, with 47 million women receiving the full course of vaccine (three doses) in 2014. To evaluate the potential impact of HPV vaccines in the reduction of HPV-related disease, we aimed to estimate the HPV type distribution and burden of anogenital and head and neck cancers attributable to HPV types (HPVs 16/18/31/33/45/52/58/6/11) included in currently licensed HPV vaccines. Methods: In all, 18 247 formalin-fixed paraffin-embedded specimens were retrieved from 50 countries. HPV DNA detection and typing were performed with the SPF-10 PCR/DEIA/LiPA25 system. With the exception of cervical cancer, HPV DNA-positive samples were additionally subjected to HPV E6*I mRNA detection and/or p16 INK4a immunohistochemistry. For cervical cancer, estimates were based on HPV DNA, whereas for other sites, estimates were based on HPV DNA, E6*I mRNA, and p16 INK4a biomarkers. Results: The addition of HPVs 31/33/45/52/58 to HPVs 16/18/6/11 in the nonavalent HPV vaccine could prevent almost 90% of cervical cancer cases worldwide. For other sites, the nonavalent HPV vaccine could prevent 22.8% of vulvar, 24.5% of penile, 60.7% of vaginal, 79.0% of anal cancers, 21.3% of oropharyngeal, 4.0% of oral cavity, and 2.7% of laryngeal cancer cases. Conclusions: Our estimations suggest a potential impact of the nonavalent HPV vaccine in reducing around 90% of cervical cancer cases and a global reduction of 50% of all the cases at HPV-related cancer sites.